Understanding the Influencing Factors of Pro-Environmental Behavior in the Hotel Sector of Mauritius Island - Toshima Makoondlall-Chadee; Chandradeo Bokhoree (Tourism and Hospitality)
This quantitative study explored the factors influencing pro-environmental behavior (PEB) among hotel guests by integrating the Theory of Planned Behavior (TPB) with additional constructs. Data were collected from a sample of hotel guests through surveys and analyzed using both SPSS for inferential statistics and Partial Least Squares Structural Equation Modeling (PLS-SEM) for structural equation modeling. The analysis involved the assessment of measurement and structural models to ensure reliability and validity. The results revealed significant relationships between attitudes, subjective norms, perceived behavioral control, and behavioral intention toward PEB. Additionally, environmental knowledge and normative beliefs were found to play critical roles in shaping guests’ intentions. Using both SPSS and PLS-SEM provided a comprehensive understanding of the factors affecting PEB, confirming the proposed hypotheses and offering insights for promoting sustainable practices in the hospitality industry.